Overexpression of leukotriene C4 synthase in bronchial biopsies from patients with aspirin-intolerant asthma. - Cowburn, A S (1998)
Aspirin causes bronchoconstriction in aspirin-intolerant asthma (AIA) patients by triggering cysteinyl-leukotriene (cys-LT) production, probably by removing PGE2-dependent inhibition. To investigate why aspirin does not cause bronchoconstriction in all individuals, we immunostained enzymes of the leukotriene and prostanoid pathways in bronchial biopsies from AIA patients, aspirin-tolerant asthma (ATA) patients, and normal (N) subjects. Counts of cells expressing the terminal enzyme for cys-LT synthesis, LTC4 synthase, were fivefold higher in AIA biopsies (11.5+/-2.2 cells/mm2, n = 10) than in ATA biopsies (2.2+/-0.7, n = 10; P = 0. 0006) and 18-fold higher than in N biopsies (0.6+/-0.4, n = 9; P = 0. 0002). Immunostaining for 5-lipoxygenase, its activating protein (FLAP), LTA4 hydrolase, cyclooxygenase (COX)-1, and COX-2 did not differ. Enhanced baseline cys-LT levels in bronchoalveolar lavage (BAL) fluid of AIA patients correlated uniquely with bronchial counts of LTC4 synthase+ cells (rho = 0.83, P = 0.01). Lysine-aspirin challenge released additional cys-LTs into BAL fluid in AIA patients (200+/-120 pg/ml, n = 8) but not in ATA patients (0. 7+/-5.1, n = 5; P = 0.007). Bronchial responsiveness to lysine-aspirin correlated exclusively with LTC4 synthase+ cell counts (rho = -0.63, P = 0.049, n = 10). Aspirin may remove PGE2-dependent suppression in all subjects, but only in AIA patients does increased bronchial expression of LTC4 synthase allow marked overproduction of cys-LTs leading to bronchoconstriction.